The Effect of Training, Integrity and Competency Knowledge of Cooperation Team Official Human Resources in Directorate General of Defense Strategy the Ministry - Legionosuko, Tri; Sundari, Sri; Sutawijaya, Achmad Hidayat (International Review of Management and Marketing, 2019)
The objective of this research was to determine the effect of Training, Integrity and Teamwork Competence Knowledge of the human resources officials at the Directorate General of Defense Strategy Defense The Ministry of Defense, Jakarta in 2016. The research used survey method with quantitative approach and path analysis technique. the data were collected from 63 civil sevants as sample. sample were sellected by simple random sampling from 166 Civil servants as population. The results showed that there is the Knowledge Competency Training Effect obtained the correlation coefficient is 0.689 and the value of path coefficient of 0.374, meaning a significant path coefficient; Influence of the Knowledge Integrity, Competency obtained by the correlation coefficient is 0.651 and the value of path coefficient of 0.300, meaning a significant path coefficient; Teamwork influence on Competency Knowledge obtained the correlation coefficient is 0.704 and the value of path coefficient of 0.299, meaning a significant path coefficient; Effect of Training on Teamwork obtained a correlation coefficient of 0.598 and the value of path coefficient of 0.409. Means a significant path coefficient; Teamwork Integrity influence on the correlation coefficient 0.603 and the value of the path coefficient of 0.417. Means a significant path coefficient; and Effect of Training for the Integrity of the correlation coefficient of 0.455 and the value of the path coefficient of 0.455. Means a significant path coefficient. Keywords: knowledge competency, training, integrity, teamwork JEL Classifications: M53, O15 DOI: https://doi.org/10.32479/irmm.8852